1996
DOI: 10.1210/jcem.81.2.8636299
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bone mass as determined by ultrasound and biochemical markers of bone turnover during pregnancy and puerperium: a longitudinal study.

Abstract: In a longitudinal study, we analyzed the speed of sound (SOS) and broadband ultrasound attenuation (BUA) of the os calcis as an index of bone mineral density (BMD) to define the effects of pregnancy and lactation on bone metabolism. We used an ultrasound bone densitometer and measured 6 biochemical markers of bone turnover in 18 healthy women throughout pregnancy and puerperium. The measurement of SOS and BUA by such an ultrasound device was clinically advantageous; not only is it radiation-free technology, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 21 publications
3
20
0
Order By: Relevance
“…The measurements reflecting bone formation (osteoid surface, mineralizing surface, MAR) were markedly higher than at midpregnancy, with no change in the number of osteoclasts. The osteocalcin levels also showed dramatic increases, consistent with enhanced bone formation and similar to results from several other studies (14–15,22,32,35) . In normal bone, high resorption rates lead to high formation rates.…”
Section: Discussionsupporting
confidence: 90%
“…The measurements reflecting bone formation (osteoid surface, mineralizing surface, MAR) were markedly higher than at midpregnancy, with no change in the number of osteoclasts. The osteocalcin levels also showed dramatic increases, consistent with enhanced bone formation and similar to results from several other studies (14–15,22,32,35) . In normal bone, high resorption rates lead to high formation rates.…”
Section: Discussionsupporting
confidence: 90%
“…This increased bone resorption during early lactation was also found in cats (Liesegang & Wichert, ) and could not be prevented by a realised intake of both minerals in excess to the recommended daily allowances given by NRC () and a positive mineral balance in eight of the nine bitches. This was also shown in other species (cow: Beighle, , Holtenius & Ekelund, , Horst et al, , Rowland et al, ; man: Sowers et al, , Yamaga et al, ). It can be hypothesised that further increase of dietary mineral supply in peripartal dogs will not prevent excessively increased bone turnover but might cause adverse effects such as reduced availability of other minerals.…”
Section: Discussionsupporting
confidence: 59%
“…It undergoes a continuous process of remodeling throughout life, which involves a delicate balance between bone resorption due to osteoclast activation and new bone formation due to osteoblastic activity 1 . Some studies have reported that bone turnover increases during normal pregnancy, resulting in a reduction in bone density, 2–4 whereas others have reported an increase 5 or no change 6 in bone density during normal pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy, changes in bone metabolism occur to meet the increased calcium demand of the fetus. Bone resorption is enhanced during the third trimester of gestation and the puerperium 4 . While various studies on the increase in bone turnover using biochemical markers during normal pregnancy have been reported, there are little data published for the same conducted on preeclamptic patients.…”
Section: Introductionmentioning
confidence: 99%